Immune regulation in gastric adenocarcinoma is linked with therapeutic efficacy and improved recovery - Xu, Zhenglei; Lin, Ximin; Zeng, Haotian; Ma, Xiaoxin; Nabi, Ghulam; Abidin, Zain Ul; Wang, Luolin; Wang, Lisheng (Frontiers in Genetics, 2023)
Adenocarcinomas are one of the most common histological types of gastric cancer. It has been ranked fifth among common cancers and is the third among death causing cancers worldwide. The high mortality rate among patients with gastric cancer is because of its silent evolution, genetic heterogeneity, high resistance to chemotherapy as well as unavailability of highly effective therapeutic strategy. Until now a number of several treatment strategies have been developed and are being practiced such as surgery, chemotherapy, radio therapy, and immunotherapy, however, further developments are required to improve the treatment responses and reduce the side effects. Therefore, novel personal therapeutic strategies based on immunological responses should be developed by targeting different check points and key immune players. Targeting macrophages and related molecular elements can be 2 useful to achieve these goals. In this minireview, we discuss the available treatment options, molecular underpinnings and immunological regulations associated with gastric adenocarcinoma.We further describe the possible check points and immunological targets that can be used to develop novel therapeutic options.